Cost-effectiveness analysis of pembrolizumab plus chemotherapy versus chemotherapy in untreated advanced pleural mesothelioma in the Chinese healthcare system - Wenwang Lang; Yulong He; Changchun Hou; Hua Li; Qinling Jiang; Liuyong Mei (Frontiers in Pharmacology)
ObjectiveThe combination of pembrolizumab and chemotherapy has demonstrated notable clinical advantages in improving overall survival than chemotherapy alone for patients with untreated advanced pleural mesothelioma. The purpose of this study was to assess its cost-effectiveness.Materials and methodsA Markov state-transition model was constructed using data from the IND227 phase 3 randomized clinical trial. Utility values for health states were taken from the IND227 trial, and direct medical costs were from the pertinent literature and local pricing data. Outcomes measured included quality-adjusted life years (QALYs), incremental cost-effectiveness ratio (ICER), incremental net health benefit (INHB), and incremental net monetary benefit (INMB). To manage the uncertainty in the model, both probabilistic sensitivity analysis (PSA) and one-way sensitivity analysis (OWSA) were used.ResultsIn the base-case analysis, pembrolizumab plus chemotherapy resulted in an incremental gain of 0.23 QALYs at an additional cost of $18,199.63, resulting in an ICER of $80,557.23/QALY. This was not favorable compared to China’s willingness-to-pay (WTP) threshold of $38,042.49/QALY, with an INHB of −0.25 QALYs and an INMB of $-9,605.00. Subgroup analyses showed ICERs for pembrolizumab plus chemotherapy versus chemotherapy of $33,917.61 and $99,536.73 in non-epithelioid and epithelioid patients, respectively. PSA indicated probabilities of cost-effectiveness for pembrolizumab plus chemotherapy at 0.55%, 69.41%, and 0.14% for the entire population and the non-epithelioid and epithelioid subgroups, respectively.ConclusionIn the Chinese healthcare system, the combination of pembrolizumab and chemotherapy did not prove to be more cost-effective than chemotherapy alone as an initial treatment for untreated advanced pleural mesothelioma, with the exception of patients who have non-epithelioid histology.